DAMPAK MOTIVASI PADA KINERJA KARYAWAN DI ERA NEW NORMAL COVID-19: English - Afiah Mukhtar; Harenal Daeng Toto; Nurdiana Nurdiana; Masradin Masradin; Asmawiyah Asmawiyah (Jurnal Manajemen Perbankan Keuangan Nitro, 2022)
This study aims to determine the effect of motivation on employee performance in the new normal condition of covid-19. The data used are primary and secondary data, namely data sourced from direct observations and interviews with company respondents located in the city of Makassar engaged in the sale of building materials distributors. The analytical method used is descriptive and statistical. Motivation has a significant influence on employee performance. This means that the better the motivation, the better the employee's performance. The motivation-forming indicators that are built are interpersonal communication, leadership and prove to be able to become motivational supporting factors in the new normal conditions of Covid-19